A Survey on Teachers’ Attitudes Towards Bilingual Education (Thai-Tai Yai based) for Border Schools in Mae Hong Son, Thailand - Panyawuthakrai, Rakkhun (Community and Social Development Journal, 2023)
This paper aimed to carry out a preliminary survey on teachers’ attitudes towards bilingual education (Thai-Tai Yai based) for local schools in border areas of Pang Mu areas, Mueang district of Mae Hong Son Province of Thailand, to reveal 1) the feasibility and requirements of implementing MTB program(s) in border schools; 2) the nature and implementation of MTB materials; and 3) the nature and implementation of MTB curricula. The research population was 109 teachers from 18 educational institutions. The research instruments were 1) a survey form about language and language use in schools and 2) a questionnaire consisting of five sections: basic information of the respondents; opinions on the management of bilingual education; cost and need for creating primary bilingual media, bilingual courses; and suggestions, respectively. Data were analyzed quantitatively and qualitatively by using frequency, percentage, summation, and arithmetic mean. The results were that (1) the teachers were not ready for any form and aspect of teaching instructions—having few costs and making few demands for building and creating media for bilingual instructions in five related issues as follows: solid foundational media; primary media for listening-speaking Thai; preparation for reading-writing the Thai language; development of reading-writing skills in Tai Yai language with Thai characters; and enhancement of reading-writing skills with reading materials in Tai Yai language; (2) the teachers have few costs and needs for creating a bilingual model course in their schools on eight bases, namely: educational standards; Thai/Tai Yai languages; Thai/Tai Yai cultures; local needs conformity; basic language skills; multicultural understanding, Tai Yai cultural conservation; and teaching plans in bi/multilingual education, and; (3) the teachers lack knowledge, understanding of bi/multilingualism principles, and experiences. Conclusively, bilingual (Thai-Tai Yai) education was not a ready requirement for schools in Mae Hong Son border areas.